The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1074/jbc.272.44.27823
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Putative Helix-Loop-Helix Motif in Nucleotide Excision Repair Endonuclease, XPG

Abstract: Complementation group G of xeroderma pigmentosum (XPG) is one of the most rare and pathophysiologically heterogeneous forms of this inherited disease. XPG patients exhibit varying phenotypes, from having a very mild defect in DNA repair to being severely affected, and a few cases are also associated with the neurological degeneracy and growth retardation of Cockayne's syndrome. The XPG gene encodes a 134-kDa nuclear protein that is essential for the incision steps of nucleotide excision repair. XPG protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…7) may be relevant to its incision mechanism. Also relevant may be a helix-loop-helix motif found within the I region of XPG (64). Although no evidence was found for XPG multimers in the latter study, a recombinant peptide containing this helix-loop-helix motif was able to dimerize (64).…”
Section: Consequences Of Mutating the Conserved Acidic Residues-inmentioning
confidence: 67%
See 1 more Smart Citation
“…7) may be relevant to its incision mechanism. Also relevant may be a helix-loop-helix motif found within the I region of XPG (64). Although no evidence was found for XPG multimers in the latter study, a recombinant peptide containing this helix-loop-helix motif was able to dimerize (64).…”
Section: Consequences Of Mutating the Conserved Acidic Residues-inmentioning
confidence: 67%
“…Also relevant may be a helix-loop-helix motif found within the I region of XPG (64). Although no evidence was found for XPG multimers in the latter study, a recombinant peptide containing this helix-loop-helix motif was able to dimerize (64). In the present work, co-expressed fulllength XPG protein and XPG lacking the conserved N region were found together by immunoprecipitation.…”
Section: Consequences Of Mutating the Conserved Acidic Residues-inmentioning
confidence: 73%
“…Interestingly, there are other protein interaction motifs that resemble the TPR motif in secondary structure; the paired amphipathic helix (PAH) motif, identified in certain transcription factors, (12) and the helix-loop-helix (HLH) motif, identified in transcription factors (13) and endonucleases. (14) Das et al (11) showed that the spatial arrangement of the antiparallel ␣-helices of the 14-3-3 protein resembles the arrangement of the helices within the PP5 TPR domain. The similarity in the structure of these motifs may be an example of convergent evolution toward a fundamentally important structure for protein interaction.…”
Section: Secondary and Tertiary Structurementioning
confidence: 99%
“…Three-dimensional structure data have shown that a TPR motif contains two antiparallel α-helices such that tandem arrays of TPR motifs generate a right-handed helical structure with an amphipathic channel that might accommodate the complementary region of a target protein. 4 Interestingly, there are other interaction domains that resemble the TPR motif in secondary structure; the paired amphipathic helix (PAH) motif and helix-loop-helix (HLH) motif, identified in certain transcription factors and endonucleases [6][7][8] and the antiparallel α-helices of 14-3-3 proteins. 9 The similarity in structure between these motifs most likely reflects a case of convergent evolution toward essential domains for protein interaction, which in turn may explain the abundance and functional importance of TPRs in nature.…”
Section: The Tetratrico Peptide Repeat Motifmentioning
confidence: 99%